(untitled) (Fiep Bulletin - online, 2014)
The valorization for a singular identity, starting from their multiple categories identitárias, personal or individual, gender, collective, regional or national it is present in dominant ideologies from the French Revolution with the formation of the States-nations, where an innovative reading of the formation of the caráter/identidade of a povo/nação appeared (Hobsbawm,2000). THE present study had for objective to verify in that measured the process of social representation can be constituted as agent transformer of the Imagined Community of the Capoeira, with the intention of characterizing her as element identitário aglutinador of a group to verify the Capoeira as imagined community.